(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2024)
Focusing on the feasibility study using the descriptive analytical approach by creating employees in the Saudi Telecom Company and the largest percentage of the company’s customers, where 200 items were reached, in which exceptions for the study were distributed, in which the most important results of the study: - There are reports among executives from several sectors regarding career growth, motivation, work environment, and job functions on job performance in the Saudi Telecommunications Company (STC). - There is a relationship closely linked to effective performance and diversity in the types of work and the amount of work performed by the executive directors of the key officials in the Saudi Telecommunications Company (STC). - There is a correlation between the need for a job and then the performance of Saudi Telecommunications Company (STC) employees. The study recommended important tips to mention. - Using the precise specialization of the staff and their satisfaction with the work direction. - Employees leave in discussions and meetings related to higher levels. - Reformulating promotion criteria so that they are more efficient for working employees. - Recognizing the employee’s efforts and discussing his development. - Preparing various incentives to ensure that they are distributed fairly among employees.